Probabilistic Analysis of Resistance Degradation under Corrosion - Vican, Josef; Sykora, Marian (Communications - Scientific letters of the University of Zilina, 2010)
To observe the behaviour and resistance of steel bridges with the orthotropic plate decks, the nonlinear finite probabilistic model in the ANSYS software environment was developed using software support module PDS. Random variables were described by means of parameters of probability density function according to data determined experimentally. The model takes also into account the geometrical and material nonlinearities of the structure. The major aim of the paper is to obtain the corrosion effects influence on the resistance of this structural system. Therefore the time variant loss of member resistance was computed based on selected corrosion models.